Innovation in Pediatric Clinical Education. Issue 2 (2015) - Kenyon, Lisa K.; Birkmeier, Marisa; Anderson, Deborah K.; Martin, Kathy
<x xml:space="preserve">Abstract</x> Background: At the Section on Pediatrics Education Summit in July 2012, consensus was achieved on 5 essential core competencies (ECCs) that represent a knowledge base essential to all graduates of professional physical therapist education programs. Key Points: This article offers suggestions for how clinical instructors (CIs) might use the ECCs to identify student needs and guide student learning during a pediatric clinical education experience. Pediatric CIs potentially might choose to use the ECCs as a reference tool in clinical education to help (1) organize and develop general, clinic-specific clinical education objectives, (2) develop and plan individualized student learning experiences, (3) identify student needs, and (4) show progression of student learning from beginner to intermediate to entry level. Conclusions: The ECCs may offer CIs insights into the role of pediatric clinical education in professional physical therapist education.